Teaching Spoken and Oral Comprehension Skills in Foreign Languages Classes during the COVID-19 Pandemic - Díaz Fuentes, Isela (2026)
The COVID-19 pandemic significantly impacted the educational sector including foreign language instruction, given that all fields of study resorted to Emergency Remote Education. The aim of this research was to analyze the methodological adaptation of teaching staff for teaching oral production and comprehension skills in foreign language classes. Research was conducted under a qualitative paradigm using an exploratory-descriptive approach among French, English, Japanese, Chinese, and Portuguese in Costa Rica during 2021. Data was collected through a questionnaire emailed to the target population. The collected data was analyzed through previously established thematic categories to learn about the techniques and methodology used by teachers. The information gathered revealed that teachers use a series of teaching of oral production and comprehension tools. The teaching staff made use documents in synchronous and/or asynchronous sessions. of various types of Likewise, it was found that, in order to address the aforementioned skills, the teaching staff resorted, for the most part, to the use of Information and Communication Technologies (ICT). The results revealed that the activities carried out during the ERE depended, to a large extent, on technology resources, to ensure the continuity of the teaching-learning process which, in turn, opened up new pedagogical possibilities. There was evidence of the need to consolidate teacher training in the use of ICT to promote oral skills, favoring the integration of teaching models that combine face-to-face and virtual learning in foreign language teaching.